FROM THE HISTORY OF THE ORGANIZATION OF THE HIGHER EDUCATION SYSTEM IN UZBEKISTAN (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the activities, material and technical base, staffing, and admission processes of the Tashkent State Pedagogical Institute during the 1946/47 academic year. The process of the institute's reconstruction after World War II, the restoration of the educational building, the state of the library and laboratories, the composition of the teaching staff, and admission indicators are covered based on statistical data. The study also thoroughly analyzes the problems that hindered the development of the institute, including staff shortages and shortcomings in financial incentives for students.